Gastronomic Travel Exploration Based on Healthy Traditional Beverage - Suyasa, I Gede Wiwin (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2022)
One beverage with a unique presentation from Yogyakarta is Wedang Uwuh. Besides the presentation and health benefits also interesting to become a gastronomy tourist attraction that is unknown by the tourist who comes to this city. This paper aims to reveal how and why the concoction of the sacred and highly respected Sultan became the drink of ordinary people and develop a gastronomic sightseeing tour, adopting a phenomenological hermeneutic of study of literature methods approach to enable the bracketing of literature phenomena, combined with informant interview to gain a blended analysis that brings a different perspective of wedang uwuh historical interpretation. To ensure attractiveness in developing the Wedang Uwuh Gastronomic sightseeing tour and present the uncovered narration behind Wedang Uwuh, we are adopting the gastronomic tourism component method. The result finding that this beverage is part of ordinary people's tradition and since the reign of Mataram Kingdom. Wedang uwuh has at least 14 medical benefits for health. It is a unique blend made by the courtiers of Sultan Agung when accompanying the great Sultan meditating in order to determine the location currently known as Imogiri. However, the other perspective there was a